Current treatment strategies and nanocarrier based approaches for the treatment and management of diabetic retinopathy. (28th May 2017) - Selvaraj, Kousalya; Gowthamarajan, Kuppusamy; Karri, Veera Venkata Satyanarayana Reddy; Barauah, Uday K.; Ravisankar, Vanka; Jojo, Gifty M.
Abstract: Diabetic retinopathy (DR) is a leading cause of blindness in all working age groups which contribute to patient's quality of life. Considering the anatomy and physiology of barriers in the eye, the treatment and management of pathologic ocular neovascularization in the posterior segment of the eye in DR is a challenging task. The current and emerging treatment strategies are discussed in this review for better understanding and treatment of the DR. Challenges in conventional therapy and recent developments in nanocarrier based approaches (polymeric, lipid nanoparticles, liposomes and dendrimers) and their advantages in targeting ocular tissues were also discussed in this review.